MENINGKATKAN MINAT DAN PRESTASI BELAJAR IPAS PADA SISWA KELAS IV SEKOLAH DASAR DENGAN MENGUNAKAN METODE ROLE PLAYING - Maya Dwi Hariyana; Dewi Tryanasari; Juli Sugianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by several students' problems in learning. This is based on the results of initial observations which show that students are less enthusiastic about taking science lessons and the learning carried out by teachers still uses the lecture method. To answer this, action research was carried out to improve the quality of learning carried out, namely the use of the role playing method to increase interest and achievement in science subjects for class IV students at SDN 02 Madiun Lor. The aim to be achieved in this research is that learning can be achieved well and optimally. This applies to science learning, such as being more focused on knowing your own role in the family and society, knowing the roles of other people. Therefore, role-playing activities for children will grow children's potential and interest. One of the determinants of the success of a learning process is the use of the role playing method. Because this method helps students find personal and social meaning. And with this method students learn to use the concept of roles. This research is Classroom Action Research (PTK) adapted from the Kemmis and Mc model. Taggrat. Therefore, the research was carried out in several stages. Each stage consists of planning, implementation, observation and reflection. The data collection technique uses test sheets, observation sheets and documentation. This research was carried out in two cycles. The research results obtained were, in cycle I the average value was 65,875 and completeness was 70.83%. In cycle II the average score increased to 76 and completeness was 95.83%. The data shows that students' ability to learn using the role playing method increases after learning is carried out.